Development of thalamus mediates paternal age effect on offspring reading: A preliminary investigation. Issue 14 (4th July 2021) - Xia, Zhichao; Wang, Cheng; Hancock, Roeland; Vandermosten, Maaike; Hoeft, Fumiko
Abstract: The importance of (inherited) genetic impact in reading development is well established. De novo mutation is another important contributor that is recently gathering interest as a major liability of neurodevelopmental disorders, but has been neglected in reading research to date. Paternal age at childbirth (PatAGE) is known as the most prominent risk factor for de novo mutation, which has been repeatedly shown by molecular genetic studies. As one of the first efforts, we performed a preliminary investigation of the relationship between PatAGE, offspring's reading, and brain structure in a longitudinal neuroimaging study following 51 children from kindergarten through third grade. The results showed that greater PatAGE was significantly associated with worse reading, explaining an additional 9.5% of the variance after controlling for a number of confounds—including familial factors and cognitive‐linguistic reading precursors. Moreover, this effect was mediated by volumetric maturation of the left posterior thalamus from ages 5 to 8. Complementary analyses indicated the PatAGE‐related thalamic region was most likely located in the pulvinar nuclei and related to the dorsal attention network by using brain atlases, public datasets, and offspring's diffusion imaging data. Altogether, these findings provide novel insights into neurocognitive mechanisms underlying the PatAGE effect on reading acquisition during its earliest phase and suggest promising areas of future research. Abstract : In the present study, Xia et al. demonstrate that advanced paternal age at childbirth (PatAGE) is negatively associated with offspring's reading. Moreover, this association is mediated by neuroanatomical maturation in the left posterior thalamus, which is closely linked with the dorsal attention network. These findings suggest a novel pathway through which parents affects their offspring's reading ability and suggest future avenues of research on PatAGE‐related factors, such as de novo mutation, in reading.